Correction: Cryptanalysis and improvement of an elliptic curve based signcryption scheme for firewalls. - Malik Zia Ullah Bashir; Rashid Ali (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0208857.].